The role of the music in developing the national identity: أحمد جهاد البدر (Al-Academy, 2015)
Music has a significant role in shaping the artistical, musical and national identity of individuals. The resources of the cultural identity can be divers according to the multiplicity of the social component. In Iraq, there is a unique ethnical and sacred diversity, which is rather than playing a positive role in shaping the cultural and national identity, on contrast, it is establishing to create many local identities in the same society. Each identity reflects the culture of individual ethnic or religious group, which makes people make their own decisions according to their background rather than according to the benefit of the country.Music as an important cultural source has a social function in forming an artistical identity with national aspects that can protect individuals and groups against all extremist ideas. This study discusses the shaping of musical, cultural and national identity through music education. In addition, it focusses on the awareness of the importance of the music as an essential factor in developing the personality and identity of the people. In addition, this study tries to answer two main questions:1. What is the function of the music in shaping the national identity?2. What is the role of music education in shaping the cultural and national identity?The answers of the above questions have been derived from three main topics shaped the core of this study. The first topic is ‘the aspect of the musical identity’. The second is, ‘identity in music’, and the third is ‘the relationship between the musical education and the cultural and national identity’